A Relational Sociological Analysis of Instagram in Turkey - Bal, Nazar; Kasapoglu, Aytul (Advances in Social Sciences Research Journal, 2020)
The research problem with the study that underpins this article is that Instagram manipulates the consumption habits of daily life in an intense manner. In this context, the main purpose of the article is to examine how people change their consumption habits by being affected by Instagram in daily life. In this context, answers to the questions of what Instagram and consumption mean in daily life and what are their effects were sought. Along with the globalization process and capitalism, Instagram, which is one of the popular social media tools especially in recent years, has started to affect people positively and negatively in cultural, social and economic terms. One of these effects is consumption habits. However, people's lifestyles and social identities are changing. The theoretical basis of this study is relational sociology and Pierre Bourdieu's (1984) concepts of “habitus”, “field” and “taste”. How Instagram manipulates consumption habits has been tried to be put forward with a Grounded Theory approach. In the empirical part of the study, in-depth interviews were made with 14 women who are Instagram users. Research findings reveal that the consumption habits of individuals change from utilitarian consumption to hedonist consumption. These hedonist consumption habits, on the other hand, can be said to lead people away from their own social realities and to alienate themselves and society.